Development and Evaluation of Orthographic Knowledge Awareness Scale for Children Aged 6–12 Years - Xie, Yachun; Xu, Qu; Liu, Liying; Yao, Mengmeng; Liu, Panting; Tong, Meiling; Hong, Qin; Chi, Xia (Frontiers in Psychology, 2022)
Objective: The primary purpose of this study was to develop the orthographic knowledge awareness scale for children aged 6-12 years old in Mandarin. And this study analyzed and discussed the related factors affecting children's orthographic knowledge awareness level, and provided a basis for individualized intervention to improve children's reading and writing level. Methods: Through detailed reading of literature on Chinese character orthography, combined with qualitative interviews of the target population and expert consultation, a conceptual framework for orthographic knowledge awareness of children aged 6-12 was determined. The initial version of the orthographic knowledge awareness scale contains three grade versions for grades 1-2 (210 items), grades 3-4 (207 items), and grades 5-6 (220 items), with a total of 637 items. Then, the initial scale was used to investigate children aged 6-12 in Maanshan city, Jiangsu Province, and different item screening methods were comprehensively used to screen items, so as to determine the formal version of the orthographic knowledge awareness scale. Finally, the official scale was used to conduct the third round of surveys of 1354 children aged 6-12 years in each of 1 ordinary primary school in 5 cities in Changzhou, Lianyungang, Nantong, Xuzhou, and Yangzhou, Jiangsu Province. And the reliability, validity and discrimination of the formal scale were tested. Results: A total of 360 items are included in the formal version of the orthographic knowledge awareness scale. The formal scale is divided into three versions for grades 1-2, 3-4, and 5-6. Each grade version consists of 120 items. The scale consists of strokes awareness test, radicals awareness test and Left-Right Reversal test. The cumulative variance contribution rates of grades 1-2, 3-4, and 5-6 are 82.47%, 61.71%, and 64.19%, respectively. The Cronbach'α coefficients of the three-grade version of the scale are 0.989, 0.946, and 0.938, the split-half reliability coefficients are 0.925, 0.766, and 0.847, and the test-retest reliability coefficients are 0.847, 0.895, and 0.8928, respectively. Conclusion: The orthographic knowledge awareness scale for children aged 6-12 years compiled in this study has good reliability and validity. The two dimensions can more comprehensively reflect the characteristics of children's orthographic knowledge discrimination.